Effect of airline travel on performance: a review of the literature - Leatherwood, W. E.; Dragoo, J. L. (British Journal of Sports Medicine, 2013)
The need for athletes to travel long distances has spurred investigation into the effect of air travel across multiple time zones on athletic performance. Rapid eastward or westward travel may negatively affect the body in many ways; therefore, strategies should be employed to minimise these effects which may hamper athletic performance. In this review, the fundamentals of circadian rhythm disruption are examined along with additional effects of airline travel including jet lag, sleep deprivation, travel at altitude and nutritional considerations that negatively affect performance. Evidence-based recommendations are provided at the end of the manuscript to minimise the effects of airline travel on performance.